68 The impact of the weekend admission on early mortality after acute coronary syndrome: a meta-analysis of observational studies. (5th June 2017) - Kwok, Chun Shing; Al-Dokheal, Mohammed; Aldaham, Sami; Rushton, Claire; Butler, Robert; Kinnaird, Tim; Zaman, Azfar; Zaman, M Justin; Timmis, Adam; Mamas, Mamas
Abstract : Background: A weekend effect where outcomes for patients admitted acutely during the weekend are worse than those for patients admitted during the week has been reported in many specialities across medicine. The evidence supporting a weekend effect among patients admitted with an acute coronary syndrome is conflicting. This systematic review and meta-analysis aims to determine if collectively there is a weekend effect in acute coronary syndrome. Methods: We searched Medline and EMBASE for cohort studies examining the association between weekend compared to weekday admission at any time of the day and early mortality (in-hospital or 30 day). Relevant studies were pooled using random effects meta-analysis for risk of early mortality. Additional analyses were performed considering only more recent studies (conducted after 2005) and by patient group (STEMI or NSTEMI) as well as meta-regression according to starting year and mean year of study. Results: A total of 26 studies were included with over 16 million participants incorporating 3.3 million weekend and over 12.5 million weekday admissions and the rates of mortality rates were 18.3% and 15.7%, respectively. The pooled results of all 26 studies suggest that weekend admission was associated with a small increase in risk of early mortality (OR 1.05 95% CI 1.03–1.07). The results for subgroups of STEMI and NSTEMI cohorts were not statistically significant and timing of admission after 2005 had minimal influence on the results (OR 1.06 95% CI 0.95–1.17). Conclusions: There is a small weekend effect for admission with acute coronary syndrome that has persisted over time.